FAMILY SAGITTIDAE GROBBEN, 1905 (CHAETONAGTHS) IN THE WATERS OF SOUTH VIET NAM - Cho, Nguyen; Trinh, Truong Si Hai; Vinh, Nguyen Tam; Lam, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2014)
Using specimens collected in the last 10 years in the waters of South Viet Nam, we have identified nine species of arrow worms of the family Sagittidae Grobben, 1905. They are Flaccisagitta hexaptera, F. enflata, Aidanosagitta neglecta, A. regularis, Ferosagitta robusta, F. ferox, Sagitta bipunctata, Zonosagitta bedoti, and Serratosagitta pacifica. The species are described in details with microscope illustration to reveal characters for identification.